Vetiver root cohesion at different growth sites in Bogor, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Fata YA, Hendrayanto, Erizal, Tarigan SD, Wibowo C. 2022. Vetiver root cohesion at different growth sites in Bogor, Indonesia. Biodiversitas 23: 1683-1692.The plant root system, including the root system of vetiver grass, plays a critical role in enhancing soil cohesion, shear strength, and vegetated slope stability. Numerous studies on mechanical reinforcement of vetiver grass-roots have been conducted, with the majority of studies focusing on ground-planted vetiver with good maintainedor naturally grown vetiver, while mechanical reinforcement of vetiver grass roots planted in landslide areas at various growth sites with less maintenance is still uncommon.The purpose of this study was to examine the vetiver grass-roots cohesion that grew in the different growth sites that had been affected by landslides. Vetiver grass root samples were collected in January 2021, at the age of 8 months. Vetiver grass roots were collected from vetiver plants growing in the affected landslide areas of (a) bareland, (b) shrubland, and (c) bushland. The root tensile strength of root samples was determined using a Universal Testing Machine (UTM) with a capacity of 3 tons, and the measurement accuracy of the load cell was 1/10000. The test was conducted in accordance with ASTM D638-14 guidelines. Three repetitions were performed on roots representing the root length class of 10 cm. The results indicated that the growth sites influenced the morphological and architectural properties of the vetiver grass-roots. The vetiver grass that grew in bushland exhibited a higher root density than bareland or shrubland. The roots were denser and had a greater range of lengths. Short roots less than 10 cm in length were the most prevalent, and the majority of them were found near the soil surface. The greater the soil depth, the less the quantity of roots.The tensile strength (TR) tends to get smaller with longer roots, and vetiver grass rootsgrew in bareland have the highestTR(15-59 MPa) relative to their growth in bushland (9-37 MPa) and shrubland (16-29 MPa). The ratio of root fiber area to root growth area (RAR) also tends to get smaller with deeper roots. Likewise, is the tensile strength increasing caused by roots (tR) and root cohesion (CR) which are a function of RAR. The CR??of vetiver roots growing in bushland (0.015-0.275 kPa) were relatively higher than those growing in bareland (0.02-0.168 kPa) and shrubland (0.002-0.028 kPa) in the same root length class, at the same depth.